Trauma and Public Memory
XII, 231 p.
Keywords: This collection explores the ways in which traumatic experience becomes a part of public memory. It explores the premise that traumatic events are realities; they happen in the world, not in the fantasy life of individuals or in the narrative frames of our televisions and cinemas.